Faktor Yang Berhubungan Dengan Kelelahan Kerja Supir Angkutan Penumpang Umum Bone–Makassar Tahun 2024 - Syam, Fauzia Aulya; H, Hasmah; Nurfaizah, Siti (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Work fatigue is a warning that the body is experiencing decline both physically and psychologically. Work fatigue affects drivers because it can result in traffic accidents. This research aims to find out or see whether there is a relationship between work period, workload, length of work and work fatigue of Bone Makassar public passenger transport drivers. The research uses analytical methods with a cross sectional approach. The number of research subjects was 80. The sample was selected using a total sampling technique with instrusments in the form of questionnaires and interviews. Data were analyzed Univariately and Bivariately.The results showed that there was a relationship between workload and work fatigue with (p-value 0.001), while the length of work and working period were not related to work fatigue that occurred in the drivers of public passenger transportation in Bone – Makassar with (p-value 0.733), (p-value 0.111) respectively.Based on the research, it was concluded that the factor related to work fatigue of public passenger transport drivers is workload. Advice for Bone – Makassar public passenger transportation drivers is expected from drivers to always set a regular rest schedule, try to have a regular and consistent work schedule. Avoid working too long or neglecting adequate rest.